Pembelajaran Kartu Permainan Berbasis Profil Pelajar Pancasila untuk Meningkatkan Pemahaman Konsep Tema Persatuan dalam Perbedaan Siswa Kelas VI SD - Eni Harjanti; Iin Purnamasari; Sumarno Sumarno (Jurnal Kualita Pendidikan, 2022)
This study aims to determine the feasibility, practicality and effectiveness of playing card learning media based on the Pancasila Student Profile in learning theme 2 unity in differences in class VI SD. This type of research is research and development. The development is carried out referring to the Sugiyono development model. The subjects of the research trial were students of class VI SDN Kreyo in the academic year 2021/2022. Consisting of 6 students of class VI in the small group trial and 21 students of class VI in the large group trial. The results of the assessments of media experts and material experts indicate that the learning media for playing cards based on the Pancasila Student Profile is feasible to use with the "Very Good" criteria. The small group trial resulted in a positive response with the criteria "Good". Large group trials were used to test the effectiveness and practicality of using game card products based on the Pancasila Student Profile. The effectiveness in terms of student learning outcomes shows that there is an average difference of 6.42 to 7.48. There is an increase in student learning outcomes as indicated by a significance value of 0.001 with a significance level of 0.005. The practicality of using game card media is shown from the teacher's observations, the percentage is 92% and the students' observations are 86.9% with each of the same practicality criteria, namely "Very Practical".